2005
DOI: 10.1074/jbc.m410175200
|View full text |Cite
|
Sign up to set email alerts
|

Parathymosin Affects the Binding of Linker Histone H1 to Nucleosomes and Remodels Chromatin Structure

Abstract: Linker histone H1 is the major factor that stabilizes higher order chromatin structure and modulates the action of chromatin-remodeling enzymes. We have previously shown that parathymosin, an acidic, nuclear protein binds to histone H1 in vitro and in vivo. Confocal laser scanning microscopy reveals a nuclear punctuate staining of the endogenous protein in interphase cells, which is excluded from dense heterochromatic regions. Using an in vitro chromatin reconstitution system under physiological conditions, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 63 publications
2
24
0
3
Order By: Relevance
“…3a). Fractionation of chromatin obtained from PADI4-introduced HEK293T cells 21 suggested that cit-H4R3 was enriched in S1 (soluble in divalent metal; transcriptional active) and S2 (soluble in EDTA; transcriptional inactive) fractions, compared with P fraction (insoluble compact chromatin) (Fig. 3b).…”
Section: Localization Of Citrullinated Histone H4 At Fragmented Nucleimentioning
confidence: 99%
“…3a). Fractionation of chromatin obtained from PADI4-introduced HEK293T cells 21 suggested that cit-H4R3 was enriched in S1 (soluble in divalent metal; transcriptional active) and S2 (soluble in EDTA; transcriptional inactive) fractions, compared with P fraction (insoluble compact chromatin) (Fig. 3b).…”
Section: Localization Of Citrullinated Histone H4 At Fragmented Nucleimentioning
confidence: 99%
“…As control we looked at the distribution of histone H1 which, as expected, was enriched in the S2 and P fractions (Fig. 4, bottom panel) (Martic et al, 2005). Strikingly, the distribution of ΔRRM-1 and F147L/F149L was strictly confined to the P fraction (Fig.…”
Section: Chromatin Distribution Of the Rrm-1 Mutantsmentioning
confidence: 99%
“…S3B) as previously described (Arrisi-Mercado et al, 2004;Ayala et al, 2006). Both mock-depleted and TDP-43-depleted HeLa cells were treated with micrococcal nuclease and subsequent extractions were performed according to standard protocols (Martic et al, 2005). We obtained three sequential fractions: S1 (chromatin soluble in divalent ions, depleted of H1), S2 (EDTA soluble, more compact chromatin), and P (chromatin enriched in actively transcribed genes and nuclear matrix components) (Fig.…”
Section: Chromatin Distribution Of the Rrm-1 Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that MTI-II affects the binding of histone H1 to the nucleosome and is likely to be involved in remodeling of the chromatin structure (20). Therefore, this protein is now thought to be a ubiquitous nuclear acidic protein that affects histone H1 function, rather than being the precursor of the thymosin ␣1 secreted peptide.…”
mentioning
confidence: 99%